1997
DOI: 10.1007/s000180050057
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of ? 2 ? 1, ? 3 ? 1 and ? 6 ? 4 integrins identifies distinct subpopulations of basal keratinocytes in the outer root sheath of the human anagen hair follicle

Abstract: The human hair follicle is composed of different concentric compartments, which reflect different programmes of differentiation. Using monoclonal antibodies against alpha 2 beta 1 and alpha 3 beta 1 integrins we demonstrated a shift in their expression, from a basolateral distribution in the basal cells of the lower outer root sheath, to an apicolateral expression in the upper outer root sheath, as in epidermis. This shift takes place in a transition zone, localized to the midpart of the follicle. The distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
3
21
0
6
Order By: Relevance
“…Laminin 5, its binding integrins and CD151 were stained by indirect immunofluorescence in human skin cryosections containing both interfollicular epidermis and hair follicles. In agreement with previous results [36], laminin 5 (Fig. 10A), integrin α6 (Fig.…”
Section: Occurrence Of Free Cd151 Under Physiological Conditionssupporting
confidence: 94%
“…Laminin 5, its binding integrins and CD151 were stained by indirect immunofluorescence in human skin cryosections containing both interfollicular epidermis and hair follicles. In agreement with previous results [36], laminin 5 (Fig. 10A), integrin α6 (Fig.…”
Section: Occurrence Of Free Cd151 Under Physiological Conditionssupporting
confidence: 94%
“…The α2β1 is found around the entire basal keratinocytes, where it is thought to mediate cell–cell interactions. ORS cells express α2β1, α3β1, and α6β4 integrins at different levels according to the region of the HF (Commo and Bernard, 1997). In vitro studies with keratinocytes and genetic manipulations in mice revealed that β1 integrins regulate adhesion and differentiation of epidermal cells and play an essential role for hair germ invagination, ORS cell migration, and sustained HM proliferation during HF morphogenesis (Brakebusch et al, 2000; Raghavan et al, 2000; Watt, 2002; Grose et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The outer root sheath cells interact with the basement membrane mainly via α 3 β 1 and α 6 β 4 integrins, which are expressed at different levels in different regions of the hair follicle [7]. …”
Section: Introductionmentioning
confidence: 99%